Beyond the recent change of opinion by the Tax Administration, what is the correct way to classify a service as digital for income tax purposes? (Forseti. Law Review, 2025)
This article analyzes the tax treatment of digital services in Peru, focusing on the interpretation of the list contained in the Income Tax Regulations. It argues that a service qualifies as digital only if it meets the essential requirements established by law. In this regard, the article seeks to reflect on the proper way to construct said list, notwithstanding the recent change in the Tax Administration’s position as set forth in Report No. 046 2025-SUNAT/7T0000.
Keywords: Digital services; Income Tax; E-commerce